Impact of banking sector competition on emerging market banks' safety and soundness – A study on Indian Banks - Sabyasachi Mohapatra; Arun Kumar Misra; Molla Ramizur Rahman (Cogent Economics & Finance, 2023)
The literature is unsettled on the simultaneous existence of Competition-Stability and Competition-Fragility phenomena in the banking system. Our study has extended the debate where we have incorporated accounting-based information along with 2-SLS system equation modeling to further explore linkages between competition, systemic risk, and stability prevailing in the Indian banking system. The study revealed that for Indian banks competition and systemic risk are inversely related. Systemic risk build-up occurs during the business growth cycle, and it spillovers onto the banking system during the economic down-cycle. The article finds that while a healthy competition would support the overall stability of banks, a fierce competition exerts competitive pressure on the banking system, and hence it negatively contributes to the bank's stability. It has supported the financial fragility hypothesis and envisages that increased capital restricts competition, and aggressive loan creation increases fragility.
Keywords: G01; G21; 330; Bank's competition; CoVar; Lerner Index; stability; systemic risk